2009
DOI: 10.1097/aco.0b013e32831a40a3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of activated recombinant factor VII in cardiac surgical patients

Abstract: At present, the generalized use of rFVIIa to prevent or to control excessive bleeding after cardiac surgery cannot be recommended. The decision to administer a potent hemostatic such as rFVIIa outside its recognized prescribing indications should be made with caution by well informed physicians and discussed with the patient. Patients should be informed about knowledge gaps and pertinent risks, which are both important in the case of rFVIIa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…Rekombinowany czynnik VIIa powinien być podawany jedynie w ramach terapii ratunkowej pacjentom z niekontrolowanymi krwawieniami, u których inne korygowalne przyczyny usunięto (np. hipotermia, niedobory czynników krzepnięcia, niedobór fibrynogenu), w związku z obawami dotyczącymi zwiększonego ryzyka zakrzepicy pomostu [290]. Zaleca się kilka strategii minimalizowania ryzyka krwawienia u pacjentów poddawanych CABG (CABG bez użycia krążenia pozaustrojowego -off pump CABG, podawanie leków antyfibrynolitycznych, hemokoncentrację, minimalizowanie aparatury do krążenia pozaustrojowego i śródoperacyjne odzyskiwanie krwi), jednak tylko kilka z nich oceniano u pacjentów z NSTE-ACS.…”
Section: Krwawienie Związane Z Pomostowaniem Aortalno-wieńcowymunclassified
“…Rekombinowany czynnik VIIa powinien być podawany jedynie w ramach terapii ratunkowej pacjentom z niekontrolowanymi krwawieniami, u których inne korygowalne przyczyny usunięto (np. hipotermia, niedobory czynników krzepnięcia, niedobór fibrynogenu), w związku z obawami dotyczącymi zwiększonego ryzyka zakrzepicy pomostu [290]. Zaleca się kilka strategii minimalizowania ryzyka krwawienia u pacjentów poddawanych CABG (CABG bez użycia krążenia pozaustrojowego -off pump CABG, podawanie leków antyfibrynolitycznych, hemokoncentrację, minimalizowanie aparatury do krążenia pozaustrojowego i śródoperacyjne odzyskiwanie krwi), jednak tylko kilka z nich oceniano u pacjentów z NSTE-ACS.…”
Section: Krwawienie Związane Z Pomostowaniem Aortalno-wieńcowymunclassified
“…However, many retrospective data analyses and systemic reviews [32], [33], [34], [35], [36], [37], [38], [39], [40] concluded that the use of rFVIIa as a rescue therapy has met with mixed results. Although showing an overall benefit for the application of rFVIIa, serious inherent publication bias associated with these reports does not support its use, at least when employed prophylactically.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported better outcome when it was given early in the course of blood loss in comparison to when it was administrated as salvage medication ( 42 - 47 ). In one cohort study, it was shown that in cardiac surgery, the response rate to control of bleeding and thromboembolic events were similar with either ≤ 40 µg/kg or ≥ 100 µg/kg doses ( 4 , 48 ).…”
Section: Discussionmentioning
confidence: 99%